Curses and Wishes : Poems - Adamshick, Carl, 1969- (Book collections on Project MUSE., 2011)
"The unusual voice encountered in Curses and Wishes carries a quiet, slightly elevated conversational tone, which flows from intimate secrets to wider social concerns. The poet has faith in economy and trusts in images to transfer knowledge that speech cannot. In Curses and Wishes the short, simple lines add up to a thoughtful book possessed with lyrical melancholy, a harmony of sadness and joy that sing: "May happiness be a wheel, a lit throne, spinning / in the vast pinprick of darkness." By the close of this ambitious work the poet has inspired readers to see the multifaceted effects of our human connections."--Page 4 of cover.